Wheat bran and second clears as supplemental energy sources for beef cows grazing winter pasture - Farmer, C.G.; Cochran, R.C.; Simms, D.D.; Heldt, J.S.; Mathis, C.P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ninety spring-calving Hereford × Angus cows grazing low-quality, tallgrass-prairie forage during the winter were fed 5 lb/day of a supplement containing combinations of wheat bran (high in digestible fiber) and second clears (high in starch). The by-product combinations accounted for 47 to 49% of each supplement, as follows: 1) 100% wheat bran; 2) 67% wheat bran, 33% second clears; and 3) 33% wheat bran, 67% second clears. Cow performance was measured by changes in body weight and body condition score. The combinations of wheat bran and second clears had no significant effects on cow performance, calf birth weights, calf performance, or cow pregnancy rates.
Keywords: Beef; Cows; Forage; Wheat; By-product